Kuusen istutusalojen varhaisperkaustarpeen estimointi - Uotila, Karri; Rantala, Juho; Saksa, Timo (Metsäntutkimuslaitos, 2013)
Seloste artikkelista: Uotila, K., Rantala, J. & Saksa, T. 2012. Estimating the need for early cleaning in Norway spruce plantations in Finland. Silva Fennica 46(5): 683–693.
Tutkimusseloste